2022
DOI: 10.7759/cureus.28309
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Neurological Manifestations of COVID-19

Abstract: The coronavirus can infect the upper respiratory tract, sinuses, and nose, and its severity manifests in its respiratory symptoms and neurological and psychological consequences. The majority of people who have COVID-19 present with moderate flu-like illness, and patients who are elderly with comorbid conditions, such as hypertension and diabetes, are more prone to experience severe illness and death. However, in the ongoing COVID-19 pandemic, neurological consequences have become a substantial source of morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Several studies have reported frequently occurring NNM linked to COVID-19. 11,12,21,22 A study by Thapa Magar et al, 21 in a sample of 3055 COVID-19 patients also documented a preponderance of similar NNM as observed in our setting, with fatigue (32%), myalgia (20%), smell and taste impairment (21%), and headache (19%) most frequently observed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several studies have reported frequently occurring NNM linked to COVID-19. 11,12,21,22 A study by Thapa Magar et al, 21 in a sample of 3055 COVID-19 patients also documented a preponderance of similar NNM as observed in our setting, with fatigue (32%), myalgia (20%), smell and taste impairment (21%), and headache (19%) most frequently observed.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have included fatigue under NNM, which we conceptualised as a constitutional symptom. 21 Researchers also found that patients without NNM were more likely to have respiratory symptoms, although there was only a trend towards significance. It was postulated, and confirmed, that URT symptoms were associated with the NNM loss of smell and/or taste as infection and inflammation in URT tissues would also be more likely to influence taste and smell.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic was caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which has continuously evolved and mutated into a range of variants with differing transmission and pathogenesis characteristics [ 1 ]. One approach to help understand acute and long-term sequelae associated with SARS-CoV-2 infection, particularly the neurological consequences [ 2 ], is to investigate the complex binding interactions of the SARS-CoV-2 virus with various receptors in the human body.…”
Section: Introductionmentioning
confidence: 99%